How body condition score affects milk production and the metabolic parameters in postpartum crossbred dairy cows raised in Amazon biome? (Research, Society and Development, 2022)
Body condition score (BCS) is a categorical variable that is widely accepted as an important tool for subjectively quantifying energy reserves in dairy cows. The aims of this study was to compare milk production and some metabolic parameters of crossbred dairy cows with low, adequate and high BCS in the recent postpartum period (PPP). This study included lactation data from 35 crossbred Girolando (Holstein × Gir) cows from calving to 90 days in milk. Cows were evaluated every 15 days for BCS, milk production, live weight, internal angle of the rump (IAR) and serum concentration of β-hydroxybutyrate (ßHB). BCS loss and nadir of the BCS in PPP were also evaluated. Cows were divided into 3 groups, as follows: High, Adequate and Low BCS, according to the BCS recommendation for cows with less than 100 days in lactation. Cows with Adequate BCS had higher milk production than cows with High BCS (P = 0.01). Cows with High BCS had the highest (P < 0.001) live weight, BCS and IAR among the groups. In addition, these cows had a higher serum ßHB concentration than cows with Adequate BCS (P = 0.001) and had the greatest loss of BCS (P < 0.001) in the PPP. The results of this study showed that Girolando dairy cows with Adequate BCS at calving had higher milk production and better metabolic condition than cows with High BCS at calving.